2003
DOI: 10.1042/bj20021238
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HTF (HER2 transcription factor) as an AP-2 (activator protein-2) transcription factor and contribution of the HTF binding site to ERBB2 gene overexpression

Abstract: The ERBB2 gene is overexpressed in 30% of human breast cancers and this is correlated with poor prognosis. Overexpression of the ERBB2 gene is due to increased transcription and gene amplification. Our previous studies have identified a new cis element in the ERBB2 promoter which is involved in the gene's overexpression. This cis element, located 501 bp upstream from the main ERBB2 transcription initiation site, binds a transcription factor called HTF (HER2 transcription factor). We report here the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 20 publications
3
66
0
Order By: Relevance
“…The absence of AP-2 in these cells could explain the result. Indeed, we have shown that AP-2 is responsible for the transcriptional activating properties of this fragment in breast cancer cells (Grooteclaes et al, 1999;Vernimmen et al, 2003). The 6 kb promoter fragment induced a comparable increase in transcriptional activity in both colorectal cell lines.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The absence of AP-2 in these cells could explain the result. Indeed, we have shown that AP-2 is responsible for the transcriptional activating properties of this fragment in breast cancer cells (Grooteclaes et al, 1999;Vernimmen et al, 2003). The 6 kb promoter fragment induced a comparable increase in transcriptional activity in both colorectal cell lines.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the 500 bp proximal ERBB2 promoter contains two AP-2 binding sites, which contribute to the gene overexpression. The first site is located 215 bp upstream from the transcription initiation site (Bosher et al, 1995), whereas the second lies 501 bp upstream from the transcription start site (Grooteclaes et al, 1999;Vernimmen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anti-actin antibody and the other reagents in the molecular studies were obtained from Sigma Chemical (St. Louis, MO). The plasmids, p756-Luc construct containing 756 bp in the hErbB2-promoter region and the AP-2 binding site mutated p756m-Luc construct were kindly provided by Dr. Winkler R. (University of Liege, Belgium) [15].…”
Section: Methodsmentioning
confidence: 99%